Research on Indigenous People and the Role of Information and Communications Technology in Development: A Review of the Literature. Issue 4 (8th November 2017) - Du, Jia Tina
Abstract: This paper presents an examination of research on Indigenous people and information and communications technology by surveying the landscape of existing studies. A literature review of the relevant 166 publications worldwide from 1995 to 2013 inclusive was performed, and bibliometrics were applied to identify the trends of research in terms of amount of yearly articles, names of authors and their affiliations, financial support status and research methods. Content analysis was used to identify major research topics. Findings show that the amount of relevant publications fluctuated almost every year, with the highest number of publications in 2007. International Information & Library Review was the most prolific journal publishing a wide range of articles in the area, and Laurel Evelyn Dyson from Australia was the most productive author. Only 9% of the publications reported explicitly that they were financially supported. Multiple empirical methods were used for the investigation, including case studies and surveys. Indigenous cultural and knowledge preservation, Indigenous literacy and education development, Indigenous people's interactions with technologies, and the digital divide issues were identified as four main research topics. On the basis of the review, future research directions from an information research perspective are discussed.